Big Data Application in Network Security Analysis - Shuai Wang; Laifu Wang; Huamin Jin; Jun Shen (Dianxin kexue)
With the rapid growth of network security information scale，how to apply big data in network security analysis has become the network security research hotspot.From the perspective of the requirement of network security analysis and insufficient of traditional technique，the necessity of introducing big data analysis technology was analyzed，and the application of big data in network security analysis was discussed from aspects of security data storage，retrieval and analysis.On this basis，the network security analysis platform based on big data was proposed，and the correlation analysis methods of typical attack scenarios were detailed.